PSYCHOANALYSIS OF THE MAIN CHARACTER IN OPPENHEIMER MOVIE BY CHRISTOPHER NOLAN - Hutabarat, Meri Kristina; Hasbi, Muh. (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study analyzes the character of J. Robert Oppenheimer in Christopher Nolan's Oppenheimer through Sigmund Freud's psychoanalysis approach. Using Sigmund Freud's psychoanalysis theory, this study explores the dynamics between the id, ego, and superego in J. Robert Oppenheimer, as well as the conflicts experienced by J. Robert Oppenheimer. The researcher analyzed these theories with a descriptive qualitative approach using the methods of narrative text study and film discourse analysis. The results show that J. Robert Oppenheimer's internal and external conflicts do not only reflect personal struggles, but also include broader themes of scientific ethics and the impact of technology on humanity. The research also identifies that J. Robert Oppenheimer's personality dynamics are complex and reflect the tension between personal ambition, moral responsibility, and social pressure. The interaction between the id, ego, and superego created deep conflict both internally and externally, influencing his decisions, behaviour, and mental health.